Virtual Homecoming Culture During the Covid-19 Pandemic for Students in Malang City - Muhammad Hasan Suryawan (Program Studi Sosiologi Universitas Nasional, 2020)
Homecoming has been a tradition of Indonesian society for decades. Those who go home are generally migrants in big cities, such as professionals, workers and even students. For students, Eid al-Fitr homecoming is the right time to take a vacation and relax with their extended family. However, this year's homecoming must be canceled and even prohibited by the government to avoid the spread of Covid-19. So that the purpose of this study is to understand the feelings and experiences of students in Malang City who are not going home due to the Covid -19 pandemic and identify other alternatives as a substitute for going home. This research uses a qualitative approach with descriptive research type. The source of data is from student immigrants in Malang City who do not do the Eid homecoming. Data collection techniques using in-depth interviews (independent interview) and observation. The data validity used triangulation between informant data. The data analysis technique used interactive analysis, namely data reduction, data presentation and conclusion drawing. The results of this study found that immigrant students in Malang City were unable to go home directly for several reasons, (1) restrictions from the government, (2) avoiding the spread of Covid-19 to their hometowns, and (3) prohibitions from their families for reasons of mutual health. . The purpose of the students homecoming in Malang is to have a vacation and stay together. For this reason, another alternative as a medium to substitute for Eid homecoming is to take advantage of sophisticated communication media such as direct face-to-face communication via video calls and taking virtual trips to tourist attractions or places in your hometown, for example using the street view feature in the google maps application. This kind of virtual homecoming certainly cannot replace students' experiences and feelings when going home directly, but the role of information technology of this kind is very important for students. Keywords : Eid al-Fitr, Virtual homecoming, students, Covid-19 pandemic.